In Vitro Effect of Aqueous Extract and Fraction IV Portion of Ximenia americana Stem Bark on Trypanosoma congolense DNA - Victor Ambrose Maikai; Beatty Viv Maikai; Patricia Ishyaku Kobo (Journal of Parasitology Research)
Trypanosomosis is a debilitating disease affecting mainly livestock and humans in tropical Africa. Chemically synthesized drugs and medicinal plants have been used in the treatment and control of this disease. In this study, the in vitro effect of aqueous extracts and fraction IV extract of Ximenia americana stem bark on Trypanosoma congolense DNA was investigated. The extracts were incubated with the parasites in vitro at 300 mg/mL aqueous extract and 25 mg/mL fraction IV portion for 30, 60, and 120 mins. The DNA of the trypanosomes was isolated and digested using ECOR1 enzyme and subsequently PCR was carried out. Results showed that aqueous extract and fraction IV portion immobilized 55% and 90% of the trypanosomes after 30-minute incubation. Subsequent isolation of the parasite DNA and agarose gel electrophoresis did not reveal that cell death was as a result of DNA fragmentation. This suggests that cell death was by another mechanism of action.